Audiogram dan Audiometri Tutur pada Lansia dengan Presbikusis - Amrollah Latupono; Eka Savitri; Abdul Kadir (Sarana Ilmu Indonesia (salnesia), 2021)
Presbycusis or age-related hearing loss (ARHL) is one of the biggest health problems suffered by the elderly that causes side effects on the physical, cognitive, emotional, behavioral, and social functions, which will contribute to social isolation, even depression. The purpose of this study was to conduct hearing screening in the elderly diagnosed with presbycusis, determine the audiogram and audiometric features, and describe the characteristics of the elderly and the results of the screening. This was a descriptive study with a cross-sectional research design. Elderly aged 60 to 99 years were screened for hearing by audiogram and speech audiometry after being diagnosed with presbycusis, to analyze the general description of the audiogram and speech audiometry. The results obtained from July to August 2018 showed 61 elderly patients with presbycusis, most were female patients (52%) and were aged 70- 79 (56%). From the right and left ear audiogram screening results, only three patients (5%) had normal audiograms. Other patients have varying degrees of sensorineural hearing loss. Most of the patients (34%) had severe hearing loss in the right ear and moderate hearing loss in the left ear (28%). Based on the speech audiometry, most of the patients (57%) had SDS between 50-80%, which means there is a problem in distinguishing words or language discrimination. This study has successfully performed hearing screening in the elderly with presbycusis. Almost all patients have sensorineural hearing loss with a minimal moderate degree of hearing loss and language discrimination disorder based on the results of the screening.